1998
DOI: 10.1200/jco.1998.16.3.872
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone versus daunorubicin in induction-consolidation chemotherapy--the value of low-dose cytarabine for maintenance of remission, and an assessment of prognostic factors in acute myeloid leukemia in the elderly: final report. European Organization for the Research and Treatment of Cancer and the Dutch-Belgian Hemato-Oncology Cooperative Hovon Group.

Abstract: In previously untreated elderly patients with AML, MTZ induction therapy produces a slightly better CR rate than does a DNR-containing regimen, but it has no significant effect on remission duration and survival. Ara-C in maintenance may prolong DFS, but it did not improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(151 citation statements)
references
References 20 publications
5
141
0
5
Order By: Relevance
“…In the effort to improve results, the standard two-drug induction approach has been varied many times in the last 15 years as regards intensity, duration and combination. [33][34][35][36] Addition of a third drug has resulted in contradictory effects. However, employment of high-dose cytarabine seems to improve outcome, 7,8,21,24,[37][38][39] without affecting the remission rates.…”
Section: Figurementioning
confidence: 99%
“…In the effort to improve results, the standard two-drug induction approach has been varied many times in the last 15 years as regards intensity, duration and combination. [33][34][35][36] Addition of a third drug has resulted in contradictory effects. However, employment of high-dose cytarabine seems to improve outcome, 7,8,21,24,[37][38][39] without affecting the remission rates.…”
Section: Figurementioning
confidence: 99%
“…When treated with conventional chemotherapy, these older patients have a 20% 2-year and 10% 5-year survival. [2][3][4][5][6][7][8] These disappointing outcomes reflect an increased frequency of poor-risk cytogenetics, a higher incidence of antecedent myelodysplasia, higher MDR1 protein expression and a limited ability to tolerate aggressive chemotherapy. 9,10 Harnessing the immune effect 11 of allogeneic hemopoietic stem cell transplantation (SCT) may improve outcome in this resistant disease, but many older patients are unsuited to conventional SCT because of increased transplant-related mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that DSF and survival results in both groups of the present study were comparable to those reported for other intensive treatment regimens in elderly AML pts. [2][3][4][5][6][7][8][9]22 This holds also true when considering all pts who reached CR or all pts registered.…”
Section: Discussionmentioning
confidence: 98%
“…In most studies, elderly AML pts receive one to three intravenous consolidation courses with reduced dosages, sometimes followed by prolonged maintenance. [5][6][7] In general, prolonged post-remission therapy does not seem to improve survival compared to short post-remission consisting of 2-3 consolidation courses only. 8 In view of the high relapse rate in older AML adults, we explored a non-infusional post-remission therapy.…”
Section: Introductionmentioning
confidence: 99%